Pelatihan Penulisan Karya Ilmiah untuk Meningkatkan Kemampuan Guru di SMP Negeri 7 Kota Bengkulu - Fina Hiasa; Amril Canrhas (Fakultas Keguruan dan Ilmu Pendidikan Universitas Maritim Raja Ali Haji, 2019)
The purpose of this service is to improve the ability of teachers at SMPN 7 Bengkulu City in writing scientific papers. The method used in this pegabdian activity is a training method by way of lectures and direct demonstrations for trainees. Participants in this activity were the board of teachers of SMP Negeri 7 Bengkulu City, totaling 13 people. The instrument used in this training was a questionnaire that was distributed to participants before and after the training to see whether or not there was an increase in the knowledge of the trainees. This training resulted in an increase in teacher knowledge about scientific work, namely knowledge of reference lists and publication journals by 55%, structure knowledge of scientific works by 40%, technical knowledge of writing scientific papers by 50%, and psychological and economic constraints by 50%.